Factors driving the population growth and decline of Portuguese cities - Barreira, A. P.; Ramalho, J. J. S.; Panagopoulos, T.; Guimarães, M. H. (Growth and Change, 2017)
Despite the worldwide trend of urbanisation, data reveal that some cities are growing whereas others are losing inhabitants. To assess such dynamics in Portuguese cities, demographic, employment, housing, and climate variables were analysed as possible drivers of population change for the period 1991–2011. Panel data models show that higher shares of employment in the secondary and tertiary sectors, higher maximum temperatures, and a higher proportion of middle-aged vacant houses act as pull factors attracting inhabitants, whereas a higher unemployment rate is a push factor for cities.